Crystal structure of afadin PDZ domain–nectin‐3 complex shows the structural plasticity of the ligand‐binding site. (13th January 2015) - Fujiwara, Yoshie; Goda, Natsuko; Tamashiro, Tomonari; Narita, Hirotaka; Satomura, Kaori; Tenno, Takeshi; Nakagawa, Atsushi; Oda, Masayuki; Suzuki, Mamoru; Sakisaka, Toshiaki; Takai, Yoshimi; Hiroaki, Hidekazu
Abstract: Afadin, a scaffold protein localized in adherens junctions (AJs), links nectins to the actin cytoskeleton. Nectins are the major cell adhesion molecules of AJs. At the initial stage of cell–cell junction formation, the nectin–afadin interaction plays an indispensable role in AJ biogenesis via recruiting and tethering other components. The afadin PDZ domain (AFPDZ) is responsible for binding the cytoplasmic C‐terminus of nectins. AFPDZ is a class II PDZ domain member, which prefers ligands containing a class II PDZ‐binding motif, X‐Φ‐X‐Φ (Φ, hydrophobic residues); both nectins and other physiological AFPDZ targets contain this class II motif. Here, we report the first crystal structure of the AFPDZ in complex with the nectin‐3 C‐terminal peptide containing the class II motif. We engineered the nectin‐3 C‐terminal peptide and AFPDZ to produce an AFPDZ–nectin‐3 fusion protein and succeeded in obtaining crystals of this complex as a dimer. This novel dimer interface was created by forming an antiparallel β sheet between β2 strands. A major structural change compared with the known AFPDZ structures was observed in the α2 helix. We found an approximately 2.5 Å‐wider ligand‐binding groove, which allows the PDZ to accept bulky class II ligands. Apparently, the last three amino acids of the nectin‐3 C‐terminus were sufficient to bind AFPDZ, in which the two hydrophobic residues are important. Abstract : PDB Code(s):3axa